Role of reduced ADAMTS13 in arterial ischemic stroke: A Pediatric Cohort Study. Issue 1 (7th December 2012) - Lambers, Moritz; Goldenberg, Neil A.; Kenet, Gili; Kirkham, Fenella J.; Manner, Daniela; Bernard, Timothy; Mesters, Rolf M.; Junker, Ralf; Stoll, Monika; Nowak‐Göttl, Ulrike
Abstract: Objective: Previous studies in adults and mice have implicated ADAMTS13 (a disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13), also known as von Willebrand factor (VWF)‐cleaving protease, as a protective factor for stroke. Here we investigated ADAMTS13 in 208 pediatric patients with arterial ischemic stroke (AIS) and 125 population‐based control children in a frequency‐matched case–control study. Methods: The proportion of patients/controls with ADAMTS13 activity levels below and above the 10th percentile was compared. Additionally, in a quintile comparison, the proportion of patients versus controls in the lowest ADAMTS13 quintile was compared to those in the 2nd to 5th quintiles. Adjustment was performed for VWF antigen (VWF:Ag), factor VIII activity (FVIII:C), blood group, and age. Results: Forty‐six of 208 patients (22%) showed ADAMTS13 levels below the 10th percentile, compared with 5 of 125 controls (4%; p < 0.001). Odds ratios/95% confidence intervals were 7.30/2.73–19.50 for the lowest percentile and 2.44/1.15–5.16 in the quintile comparison after adjustment for VWF:Ag, FVIII:C, blood group, and age. Comparing the proportion of patients with ADAMTS13 activity below the 10th percentile within the different stroke subtypes (undetermined, cardioembolic, steno‐occlusive arteriopathies), no statistically significant differences were found (undetermined, 16 of 89; cardioembolic, 6 of 40; steno‐occlusive arteriopathies, 24 of 79; p = 0.08). ADAMTS13 levels did not significantly differ among stroke subtypes ( p = 0.29). Interpretation: Our findings implicate reduced ADAMTS13 activity as a risk factor for pediatric AIS, and support the concept that ADAMTS13 has a role in the pathogenesis of pediatric AIS. ANN NEUROL 2013.